Role of Mobile Phone for English Language Teaching - Sri Yuliani (UIR Press, 2019)
Mobile phone is a recent technology in teaching English. Mobile phone provides simple and easy way in developing teaching and learning activities, therefore, the researcher was interested in finding the data information about the role of mobile phone for English language teaching. The utilization of mobile phone offers valuable opportunities for creating an effective teaching strategy. The students' perspectives are crucial for getting their views of role of mobile phone in language teaching. This case study was to find out the students' perspectives of mobile phone role in English language teaching. A qualitative design was employed for the purpose of getting the data. Mainly semi structure interview was used as the research instruments. The result of her research finding showed that most students were having good response towards the usage of mobile phones in language learning but some findings shown that the problems were also occurred at the same moment of using it. These research findings were contributed the next research for more deeply dig for language learning.